Beaches of the Gulf Coast - Davis, Richard A., Jr., 1937- (Book collections on Project MUSE., 2014)
Much of the world's population lives within thirty miles of a coast, and beaches are perhaps the most popular tourist destinations worldwide. The Gulf of Mexico is no exception: Millions of people make their homes nearby, and many of them spend considerable time at the beach, joined by millions more tourists and seasonal visitors. In Beaches of the Gulf Coast, Richard A. Davis Jr., a veteran coastal geologist, explores the dynamics of beach formation, providing the reader with a basic understanding of the characteristics and behavior of the beach environment and what cau.